This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Math 55: Discrete Mathematics UC Berkeley, Spring 2010 Solutions to Homework #5 (due on 332010) Â§ 4.1, #4: a) The statement P (1) is that 1 3 = (1(1 + 1) / 2) 2 . b) The left hand side is 1 and the right hand side is (1 Â· 2 / 2) 2 = 1 2 = 1, so P (1) holds. c) The inductive hypothesis is P ( n ), that 1 3 + 2 3 + Â·Â·Â· + n 3 = ( n ( n + 1) / 2) 2 . d) To prove the inductive step, you need to prove that if the inductive hypothesis P ( n ) is true, then P ( n + 1) is true. e) We assume the inductive hypothesis. Then, 1 3 + 2 3 + Â·Â·Â· + n 3 + ( n + 1) 3 = n ( n + 1) 2 2 + ( n + 1) 3 = n 2 ( n + 1) 2 + 4( n + 1) 3 4 = ( n 2 + 4 n + 4)( n + 1) 2 4 = ( n + 2) 2 ( n + 1) 2 4 = ( n + 1)( n + 2) 2 2 , which is the statement P ( k + 1). f) In part b, weâ€™ve shown P (1). In part e, weâ€™ve shown that P (1) implies P (2), which implies P (3), which implies P (4), and so on. For any n , this chain of implications means that P ( n ) holds. Â§ 4.1, #6: When n = 1, then 1 Â· 1! = 1 and (1 + 1)! 1 = 2 1 = 1, so the statement holds. 1 For the inductive step, suppose that the statement holds for n = k , then, for n = k + 1, the left hand side is, 1 Â· 1! + Â·Â·Â· + k Â· k ! + ( k + 1) Â· ( k + 1)! = ( k + 1)! 1 + ( k + 1) Â· ( k + 1)! = ( k + 2) Â· ( k + 1)! 1 = ( k + 2)! 1 , which is the desired formula for n = k + 1. By induction, the equation holds for all positive integers n . Â§ 4.1, #10 a) For small values, we have, 1 2 = 1 2 1 2 + 1 6 = 4 6 = 2 3 1 2 + 1 6 + 1 12 = 9 12 = 3 4 From this, I would guess that 1 1 Â· 2 + 1 2 Â· 3 + Â·Â·Â· 1 n ( n + 1) = n n + 1 b) The base case, when n = 1 was checked in part a. By induction, assume that the formula holds for n = k . Then the left hand for n = k + 1 is 1 1 Â· 2 + 1 2 Â· 3 + Â·Â·Â· + 1 k ( k + 1) + 1 ( k + 1)( k + 2) = k k + 1 + 1 ( k + 1)( k + 2) = k ( k + 2) + 1 ( k + 1)( k + 2) = k 2 + 2 k + 1 ( k + 1)( k + 2) = ( k + 1) 2 ( k + 1)( k + 2) = k + 1 k + 2 which is the equation from part a for n = k + 1. Â§ 4.1, #33: For n = 0, n 5 n = 0 0 = 0, which is divisible by 5. 2 By induction, assume that n 5 n is divisible by 5 for n = k . Then, for n = k + 1, ( k + 1) 5 ( k + 1) = k 5 + 5 k 4 + 10 k 3 + 10 k 2 + 5 k + 1 k 1 = ( k 5 k ) + 5( k 4 + 2 k 3 + 2 k 2 + k ) By the inductive hypothesis, k 5 k is divisible by 5, and the second term is divisible by 5 because it is 5 times an integer, so ( k +1) 5 ( k +1) is divisible by 5. Therefore, by induction n 5 n is divisible by 5 for all nonnegative integers n . Â§ 4.1, #50: For n = 1, the statement is that for a set of 1+1 = 2 positive integers, none exceeding 2 Â· 1 = 2, there is at least one integer that divides another. But, the only possible such set is { 1 , 2 } , and 1 divides 2....
View
Full Document
 Spring '08
 STRAIN
 Math, Mathematical Induction, Natural number, inductive hypothesis

Click to edit the document details